United States and the Middle East after the Cold War - Gamawa, Yusuf Ibrahim (American Finance & Banking Review, 2018)
The United States emerged as the most powerful country after World War II and as such found itself in an influential position to be involved in the future and destinies of many countries across the globe. The U.S. played a major role in the post War economic reconstruction in Europe and rendered assistance to many European states. American power at this time was seen to have extended to other parts of the globe, including the Middle East, which has been a region of interest to outside powers. This short paper tries to look at U.S. ambitions in the region and how far the U.S. has gone in achieving these ambitions. The paper argues that U.S. policies in the Middle East were in the long run, a failure, despite whatever successes achieved, following certain developments in the region, beginning with the 1979 revolution in Iran.